2016
DOI: 10.1097/phm.0000000000000442
|View full text |Cite
|
Sign up to set email alerts
|

Can Quantification of Biceps Peritendinous Effusion Predict Rotator Cuff Pathologies?

Abstract: Sonographically detected BPE seems to be in association with certain rotator cuff pathologies, and it can be utilized as an adjuvant finding to rule out such rotator cuff abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
17
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
(17 reference statements)
2
17
1
Order By: Relevance
“…The supraspinatus tendon and subscapularis bursa were scanned by placing the arm behind the back to shift the tendon away from the coverage of the acromion. The hand was put on the contralateral shoulder during the examination of the infraspinatus tendon and the posterior shoulder recess891013. Regarding the dynamic subdeltoid imaging test; the arm was rested beside the trunk with the transducer placed lateral to the acromion along the scapular axis.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The supraspinatus tendon and subscapularis bursa were scanned by placing the arm behind the back to shift the tendon away from the coverage of the acromion. The hand was put on the contralateral shoulder during the examination of the infraspinatus tendon and the posterior shoulder recess891013. Regarding the dynamic subdeltoid imaging test; the arm was rested beside the trunk with the transducer placed lateral to the acromion along the scapular axis.…”
Section: Methodsmentioning
confidence: 99%
“…Subluxation of the biceps tendon was diagnosed if part of the tendon was displaced from the bicipital groove, whereas dislocation was diagnosed if the whole tendon was outside the groove. A full-thickness tear of the rotator cuff tendons was defined as an intra-tendinous gap extending from the bursal to the articular aspect, while a partial thickness tear was defined as a gap on either side or inside the tendon89101315. One antecedent study indicated that simultaneous presentation of BPE with subdeltoid bursa effusion usually coexisted with rotator cuff tendon tears16.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations